Exploring the influence of silver and lead on structure and function of xylanase: spectroscopic and calorimetric methods. Issue 3 (7th May 2020) - Jing, Mingyang; Tang, Rui; Han, Guangye; Zhang, Shansheng; Liu, Rutao
Abstract: Soil contamination with heavy metal could induce the alteration of soil ecological environments, and soil enzyme activities are sensitive indicators for the soil toxicology. Xylanase is one of predominant soil enzymes related to carbon nitrogen cycle. In this work, we explored the underlying mechanisms for conformational and enzymatic activity alterations of xylanase after silver and lead exposure at molecular level with systematical measurements including multiple spectroscopic methods, isothermal titration calorimetry, and enzymatic activity. Both silver and lead could loosen and unfold the skeleton of xylanase with the quenching of endogenous fluorescence. Silver interacted with xylanase forming larger-size aggregations through Van der Waals forces and hydrogen bonding, while lead interacted with xylanase forming larger-size aggregations through hydrophobic force. Silver and lead induced an obvious loss (67.1 and 56.31%) of the xylanase enzymatic activity, but silver has a greater impact on xylanase than that of lead. The xylanase enzymatic activity significantly decreased due to the conformational alterations. The negative effect of silver exposure on xylanase structure and function was more prominent than that of lead. Graphical Abstract: